CRITERIA FOR THE SELECTION OF CIRCUMSTANCES USED AS A SIGNS QUALIFYING THE CRIME - Zakomoldin, R.V; Kondratyuk, S.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Every crime is committed under certain circumstances that characterize the objective and subjective signs of this crime. Accordingly, the basis of the signs qualifying the crime are the specific circumstances of the crime committed. In addition, each feature indicates not one, but a whole group of possible circumstances. Thus, the commission of a crime as a fact and a process is characterized by many circumstances. Therefore, in the process of differentiation of criminal responsibility, the legislator is faced with the problem of choosing, evaluating and regulating those circumstances that can later be synthesized into the main part of a crime as its criminating characteristics or highlighted as qualifying and especially qualifying characteristics. This process should be streamlined in a certain way, in accordance with a unified concept and a specific set of criteria and conditions. The authors formulate uniform criteria for the selection of such circumstances for their regulation in criminal law as signs that qualify a crime.